Techno-economic analysis of solar thermal power plants using liquid sodium as heat transfer fluid. (1st January 2019) - Fritsch, Andreas; Frantz, Cathy; Uhlig, Ralf
Highlights: A techno-economic analysis of solar thermal power plants using sodium. Comparison of sodium and molten salts as heat transfer fluid. High heat flux density of the sodium receiver results in a higher receiver efficiency. LCOE assessment indicates a significant cost reduction potential by using sodium. Abstract: Solar thermal power plants with central receiver and thermal storage are expected to be one key technology in future electricity generation, because they are renewable and due to the thermal storage independent of the current solar radiation. State-of-the-art solar power plants often use molten nitrate salts as heat transfer fluid. The use of liquid sodium instead leads to lower electricity generation costs. Sodium has a high thermal conductivity and thus large heat transfer rates are possible. Hence, a smaller absorber surface is sufficient for the same thermal power. As a result, the sodium receiver achieves a higher efficiency at lower investment cost. Additionally, the aiming strategy, which reduces the peak heat flux on molten salt receivers isn't necessary for sodium. Even at high heat flux densities, the absorber tubes will be cooled sufficiently due to the high heat transfer coefficients. Therefore, the sodium receiver in this analysis is designed for one single aim point, resulting in a heat flux density of q ̇ mean = 1.06 MW / m 2 and q ̇ peak = 2.99 MW / m 2 . The state-of-the-art system with molten salt considers q ̇ mean = 0.51 MW / m 2 and q ̇ peak = 1.0 MW / m 2 . The presented techno-economic analysis of two sodium based concepts compared to a reference system with molten salt results in up to 16% lower electricity generation costs.